Asuransi Kesehatan Sosial dan Biaya Out of Pocket di Indonesia Timur - Isak Iskandar Radja; Hari Kusnanto; Mubasysyir Hasanbasri (Center for Health Policy and Management, 2015)
Background: Social health insurance in Indonesia is carried by social insurance mechanism aims to provide social security protection to the community so their basic health needs can be met adequately. Social insurance is expected to increase access and utilization of health services as well as reducing the risk of out-of-pocket expenditure (OOP) that resulting in catastrophic expenditures and poverty. Objective: To analyze the utilization of inpatient care, health insurance and hospitalization OOP expense ratio based on living area, type of health facility and type of social health insurance in Eastern Indonesia. Methods: This study uses secondary data analysis using Indonesian Family Life Survey East 2012 data. This is a quantitative approach using cross-sectional design, and multivariate analysis using linear regression at 95% confidence level. Results: The use of hospitalization in Eastern Indonesia by insurance users is 54.6%, while those who do not use insurance is 45.4%. A total of 24.6% insurance owner do not use insurance at the time of hospitalization. Multivariate analysis showed no significant difference in the cost of hospitalization OOP based living area and type of health facility. OOP costs of hospitalization for Jamsostek/other members were higher than Askes and Jamkesmas members. Conclusion: The government needs to implement a social health insurance system that is of a better quality and comprehensive in order to protect users from the burden of high health care cost. Latar belakang: Jaminan kesehatan sosial di Indonesia dilakukan dengan mekanisme asuransi sosial bertujuan untuk memberi jaminan perlindungan sosial kepada masyarakat agar dapat terpenuhi kebutuhan dasar hidupnya secara layak, khususnya di bidang kesehatan. Asuransi sosial diharapkan dapat meningkatkan akses dan utilisasi pelayanan kesehatan serta mengurangi resiko pengeluaran biaya out of pocket (OOP) yang bisa berdampak pada pengeluaran katastropik serta kemiskinan. Tujuan: Menganalisis pemanfaatan rawat inap, asuransi kesehatan dan perbandingan biaya OOP rawat inap berdasarkan area tinggal, jenis fasilitas kesehatan dan jenis asuransi kesehatan sosial di Indonesia Timur. Metode: Penelitian ini menggunakan metode analisis data sekunder dengan sumber data Indonesian Family Life Survey East 2012. Pendekatan kuantitatif dengan rancangan cross sectional. Analisis multivariat menggunakan regresi linier pada tingkat kepercayaan 95%. Hasil: Pemanfaatan rawat inap di Indonesia Timur oleh pengguna asuransi sebesar 54,6% sedangkan yang tidak menggunakan asuransi sebesar 45,4%. Sebanyak 24,6% pemilik asuransi tidak menggunakan asuransinya pada saat kunjungan rawat inap. Hasil analisis multivariat menunjukkan tidak ada perbedaan biaya OOP rawat inap yang signifikan berdasarkan area tinggal dan jenis fasilitas kesehatan. Biaya OOP rawat inap pengguna Jamsostek/lainnya ternyata lebih tinggi dari pengguna Askes dan Jamkesmas. Kesimpulan: Pemerintah perlu menerapkan sistem asuransi kesehatan sosial yang lebih bermutu dan komprehensif agar dapat melindungi penggunanya dari beban biaya kesehatan yang tinggi, agar utilisasi asuransi kesehatan lebih berkualitas di masa mendatang.